Impacts of 3D visualizations and virtual reality in display designs for remote monitoring of satellite operations - Buchner, Savannah L.; Rindfuss, Abigail; Wood, Jennifer; Schaub, Hanspeter; Hayman, Allison P. (Frontiers in Virtual Reality, 2025)
IntroductionRemote supervision and monitoring of autonomous systems is an important modality for future operations including spaceflight, manufacturing, and transportation. However, monitoring presents many challenges for the operator, which may be reduced through novel interfaces and display design. Virtual reality (VR) shows promise for direct control teleoperation paradigms, but it is unclear if VR is useful for future supervisory paradigms that will primarily involve monitoring systems rather than directly controlling them. This paper investigates the impacts of 3D visualizations and VR in displays for the remote monitoring of a satellite servicing mission.MethodsThree different displays, with different degrees of 3D visualizations and immersion, are compared through human subject testing (n = 33) on factors of situation awareness, workload, usability, and subjective utility. These displays include an immersive, visualization based VR display, a non-immersive screen-based 3D visualization, and a nonimmersive, non-visualized baseline display.ResultsVisualizations improve level 2 (comprehension, p = 0.009) and level 3 (projection, p = 0.014) situation awareness, and VR reduces level 1 situation awareness (perception, p < 0.005). No differences are found among workload, usability, and utility; however, the results of subjective utility are trending towards significance (p = 0.069).DiscussionThis research indicates there are benefits to including visualizations for display design for remote monitoring of satellites, but these initial results find little evidence that VR provides additional benefits.